Rainbows and "Ready for Residency": Integrating LGBTQ Health Into Medical Education - Lauren T. Roth; Suzanne Friedman; Rachel Gordon; Marina Catallozzi (Association of American Medical Colleges, 2020)
Introduction To provide appropriate and sensitive care for lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) youth, providers must learn specific skills and guidelines. Most medical schools lack formal education on LGBTQ health, particularly for adolescent patients. Methods We developed an Introduction to LGBTQ Health course for fourth-year medical students as part of a monthlong Ready for Residency curriculum in March and April of their graduating year. The course addressed guidelines recommended in the care of LGBTQ individuals utilizing problem-based learning methodology. Through learner-led discussion, students worked in small groups to research case-based scenarios and reported their findings to the larger group, followed by teaching points from a facilitator. The course was evaluated on curricular perception using a 5-point Likert scale and open-ended feedback. Results One hundred forty-six students participated in the curriculum; 103 completed the session evaluation. Mean total scores were 4.6 out of 5 in March and 4.7 out of 5 in April after changes were made based on student feedback, namely, increasing the session from 50 to 80 minutes and decreasing session size from 72 students to 36. Students felt the session was well planned and run, engaging, and relevant; appropriately integrated evidence-based medicine; and taught them what they hoped to learn. Discussion Many medical schools lack curricula dedicated to LGBTQ health care. Implementing this mandatory LGBTQ health course was well received and highly rated by almost all students regardless of anticipated specialty. The session could be easily replicated at medical schools across the country.